First-line lesional aspiration in acute stroke thrombectomy using a novel intermediate catheter: Initial experiences with the SOFIA - Kabbasch, Christoph; Möhlenbruch, Markus Alfred; Stampfl, Sibylle (Interventional neuroradiology, 2016)
IntroductionFive randomized controlled trials (RCTs) on endovascular therapy (EVT) of stroke have proven a clinical benefit over conservative treatment or IV-thrombolysis alone. Lesional clot aspiration with a dedicated system can achieve revascularization without an additional retriever (a direct-aspiration first-pass technique, ADAPT), and the SOFIA has been shown to be both safe and efficacious in a multicentric retrospective study. We have evaluated a subset of these data acquired in two major stroke centers with regard to using the SOFIA for first-line lesional aspiration.MethodsThirty patients with large-vessel occlusions treated with first-line lesional aspiration were identified. Procedural data, clot length, reperfusion success (mTICI), procedural timings, complications, and clinical status at admission, discharge and at 90 days were analyzed.ResultsThe median baseline NIHSS was 16. IV thrombolysis was administered in 15/30 patients. Ninety-three percent of occlusions were in the anterior circulation. TICI?≥?2b was achieved in 90% of multimodality treatments; lesional aspiration was successful in 67% within a median time of 20 minutes. The highest first-attempt success rate was in MCA occlusions (median time to recanalization 10 minutes). There were no device-related events. Symptomatic intracerebral hemorrhage (sICH) occurred in 10%, but never with sole lesional aspiration. Embolization to new territories was recorded in 1/30 (3%). Median discharge NIHSS was 7; 30% were mRS?≤?2 at discharge and 43% at 90-day follow-up.ConclusionsLesional aspiration with SOFIA is in line with published data. The SOFIA may be used as a first-line device, aiming at fast recanalization by sole aspiration with good safety and efficacy. If unsuccessful, it converts into part of a stent retriever-based multimodality treatment.